Open innovation and performance in the service sector - Vincenzi, Ticiana Braga De (2021)
Purpose – Organizations that decide to invest in innovation must define how this will be done: internally,externally or in a hybrid way, developing internal research and establishing partnerships with other agents ofthe innovation system. This paper aims to analyze whether the service companies’ intensity of openness andinnovation efforts are related to their innovative and financial performances. Open innovation assumes thatorganizations should use external and internal resources as they develop new technologies.Design/methodology/approach – The study used data from the survey of technological innovation(Pintec). As regards innovations, it was considered the commercial and operational innovation performancesand the innovative novelty performance. As regards financial performance, it was considered the overall netsales per employee. The intensity of open innovation was measured by the combination of breadth and depth(diversity and importance of the interfaces). The innovative effort was measured by spending on innovationactivities. Regressions were applied to evaluate a set of hypotheses.Findings – The results indicate that companies with a greater orientation toward open innovationpresented better scores. The results also lead to the conclusion that foreign firm ownership structure andbeing part of a corporate group were the factors that caused the greatest impact on financial performance inthe service sector.Practical implications – The study provides empirical data on the importance of open innovation inimproving organizations’ performance, especially the breadth of open innovation.Originality/value – The study contributes to expanding the research field addressing the relationshipbetween service innovation and performance